Development of PPKn Learning Based on an Android Application through Google Sites at SMA Negeri 1 Lembar - Zakaria, Rendi; Mustari, Mohammad; Sawaludin, Sawaludin; Alqadri, Bagdawansyah (UNDIKMA, 2024)
This study aims to develop a product in the form of Civic Education (PPKn) learning media based on an Android application using Google Sites. The research method used is Research and Development (R&D) with the ADDIE development model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The results of the study, based on the evaluation of three validators—media experts, language experts, and content experts—show that the validation by media experts obtained a percentage of 93.9%, validation by language experts received 77.5%, and validation by content experts reached 92.2%. The average of the three expert evaluations is 88.1%, indicating that the Google Sites application media product is highly feasible for further development, as it falls within the 81-100% range on the Likert scale. Feedback from users, including teachers and students, showed that the teachers' response reached 81.6%, while the students' response reached 97.7%. Based on this data, it is concluded that the Civic Education (PPKn) learning media based on an Android application through Google Sites is highly feasible for use in the teaching and learning process in schools.